2012
DOI: 10.1371/journal.pone.0033533
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Responsive Olfactory Uptake of Manganese Improves Motor Function Deficits Associated with Iron Deficiency

Abstract: Iron-responsive manganese uptake is increased in iron-deficient rats, suggesting that toxicity related to manganese exposure could be modified by iron status. To explore possible interactions, the distribution of intranasally-instilled manganese in control and iron-deficient rat brain was characterized by quantitative image analysis using T1-weighted magnetic resonance imaging (MRI). Manganese accumulation in the brain of iron-deficient rats was doubled after intranasal administration of MnCl 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 39 publications
7
65
0
Order By: Relevance
“…Manganese neurotoxicity resembles Parkinson's disease and has been well-documented in people drinking contaminated water, workers employed in mining and Mn ore processing and agricultural workers exposed to Mncontaining pesticide [13]. The use of methylcyclopentadienyl manganese tricarbonyl (MMT), an octane enhancer in gasoline, continues to be a huge concern about potential neurological damage due to inhalable Mn particles after combustion [14] Mn intoxication has also been observed in children under long-term parenteral nutrition and patients with chronic liver diseases [15].Advances in molecular physiology and toxicology have revealed that Mn neurotoxicity is, at least, mediated by dopaminergic dysfunction [16][17][18][19]. The dopaminergic neurotransmission is also impaired by iron deficiency.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Manganese neurotoxicity resembles Parkinson's disease and has been well-documented in people drinking contaminated water, workers employed in mining and Mn ore processing and agricultural workers exposed to Mncontaining pesticide [13]. The use of methylcyclopentadienyl manganese tricarbonyl (MMT), an octane enhancer in gasoline, continues to be a huge concern about potential neurological damage due to inhalable Mn particles after combustion [14] Mn intoxication has also been observed in children under long-term parenteral nutrition and patients with chronic liver diseases [15].Advances in molecular physiology and toxicology have revealed that Mn neurotoxicity is, at least, mediated by dopaminergic dysfunction [16][17][18][19]. The dopaminergic neurotransmission is also impaired by iron deficiency.…”
mentioning
confidence: 99%
“…Treating adult rats and mice with Mn also increases the number of D 2 binding sites in the dorsal striatum [27]. In addition, rats exposed to Mn during PND 1-21 demonstrated a significant reduction in DAT levels that can persist into adulthood [19,28].An accumulating body of evidence has indicated that Mn absorption is enhanced in iron-deficient anemia (IDA) due to iron-responsive up-regulation of divalent metal transporter-1 (DMT1) which is expressed in intestinal and olfactory epithelium [17,[29][30][31]. Our previous study demonstrated that iron deficiency impairs motor coordination, which was corrected by olfactory Mn exposure, suggesting a possibility that Mn could modulate or compensate for some detrimental effects resulting from an irondeficient state [17].…”
mentioning
confidence: 99%
See 3 more Smart Citations